Breeding, Improvement and Germplasm Conservation of Medicinal and Aromatic Plants - a Review - Verma, S. K.; Sharma, S. K.; Singh, Charan; Mehta, H. (Indian Forester, 2004)
Medicinal plants have a long history of their association with humankind since time immemorial. Indian, Chinese and the other oriental systems of medicines are dependent on medicinal plants besides the traditional use of a range of plants as medicines by tribals living in the forests as has been brought out in different ethno-botanical studies. The Asiatic flora includes tropical, sub-tropical and temperate species used in modern medicines and aroma industries. The genetic erosion rates of medicinal flora are alarming leading to shrinking biodiversity and this calls for invoking all feasible breeding methods and strategies to increase genetic variation and augment it to conservation of already existing variation. The methods of conservation could be in-situ and ex-situ. Among in-situ conservation, natural reserves, forest reserves, national parks etc. are included while in ex-situ (off site) conservation, gene banks, herbal garden, seed orchards and in-vitro methods of conservation viz. shoot culture and plant cell suspension culture are included. The advents of molecular tools have opened up new vistas of mobilizing genes across genera and texa and plant improvement through marker assisted selection (MAS). These new techniques along with already existing time-tested methods can be useful complements for future germplasm improvement and conservation.